SUFI PRACTICES IN CONTEMPORARY KAZAKHSTAN: TRADITIONS AND INNOVATIONS - TEMIRBAYEVA, Aigerim; TEMIRBAYEV, Talgat; KAMAROVA, Ruziya; TYSHKHAN, Kenshilik (CENTRAL ASIA AND THE CAUCASUS, 2021)
We deemed it necessary to write about the Sufi tradition in Kazakhstan and its unfolding transformation into new practices. Religious revival in Kazakhstan has made Sufism, its teaching and practices very attractive. Its traditions have survived in the Soviet past and were revived in post-Soviet Kazakhstan. Pilgrimage to holy places, first and foremost within Kazakhstan, and veneration of saints have gained popularity as prominent features of Sufism. The same process is unfolding in the neighboring states—in Uzbekistan, Kyrgyzstan, the North- ern and Southern Caucasus, and Turkey.In Soviet times, in Kazakhstan, how- ever, the Sufi tradition was partly crushed by repressive secularization practiced by Sovi- et authorities, which explains why Sufism is sometimes revived in the form of pseudo Sufi teachings.Sufism is a multi-dimensional phenomenon, therefore, the forms of its revival should be studied in depth to tap its spiritual and moral potential for the purposes of our country’s cultural development. No wonder that Sufism and its profound spiritual teaching of Islamic mysticism have stirred up a lot of interest in both Muslim and Christian regions in the country’s western part.The article examines the forms of revival, traditions and transformations of Sufism in our country. In our analysis we relied on scientifically proven information from open academic sources and our field studies carried out using the methods of participant observation and in-depth interviews.